Hiérarchies au sein des mouvements féministes en Iran. Marginalisation des femmes des minorités ethniques dans la production féministe académique et militante - Somayeh Rostampour (Genre, Sexualité et Société)
This article aims to analyze the ethnic differentiations and social hierarchies that are deeply rooted in the feminist movements that emerged in post-war Iran (from 1990 to 2017). From the standpoint that comprehends class and ethnicity in their dialectical unity, I will critically examine both the theoretical premises as well as the political implications of dominant strands of Iranian feminism, dubbed here as “centralist reformist feminism”. Specifically, the article focuses on the discourse and the political praxis of one of the most influential feminist movements, namely “One Million Signatures for the Repeal of Discriminatory Laws” that were formed in 2006 in support of changing misogynist laws against women. In addition, five interviews are also conducted with the “ethnic-minority” ex-members of the Campaign, whose immediate political experiences have massively contributed to the richness of this field work. This article concludes that the “centralist feminist”, despite its merits, is primarily constructed based on the social privileges, historical experiences, and political demands of Shia and Persian women who belong to the urban and upper middle classes. Hence, this mode of feminism reproduces the nationalist presuppositions of the Islamic Republic regime and thus marginalizes the social struggles of ethnic-women minorities.